Kepemimpinan Penghulu dalam Pelaksanaan Program Pemberdayaan Budidaya Ikan Lele di Kampung Sungai Tengah Kecamatan Sabak Auh Kabupaten Siak - Rahayu Rahayu; Khairul Rahman (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The leadership of the village head plays a strategic role in determining the effectiveness of community empowerment programs in rural development. This study examines the leadership of the Penghulu in implementing the catfish farming empowerment program in Sungai Tengah Village, Sabak Auh District, Siak Regency. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation involving the village head, the Village Consultative Body (BPKam), the program coordinator, and members of catfish farming groups. Data were analyzed using the interactive model of Miles and Huberman, while source triangulation ensured data credibility. The findings indicate that the Penghulu demonstrated effective leadership by promoting participatory planning through village deliberations, establishing clear task distribution among farming groups, and facilitating the provision of seeds, feed, and farming facilities. Leadership was further reflected in continuous communication, motivation, and institutional support that encouraged community participation. Despite these achievements, program implementation remained constrained by technical challenges in fish cultivation, limited field supervision, ineffective communication between stakeholders, and security issues related to fish theft. Strengthening supervisory mechanisms, communication, and collaborative management is therefore essential to improve the sustainability and effectiveness of community-based aquaculture empowerment programs.